The Gut Microbiome Is Associated With Therapeutic Responses and Toxicities of Neoadjuvant Chemoradiotherapy in Rectal Cancer Patients—A Pilot Study - Shi, Wei; Shen, Lijun; Zou, Wei; Wang, Jingwen; Yang, Jianing; Wang, Yuezhu; Liu, Bingdong; Xie, Liwei; Zhu, Ji; Zhang, Zhen (Frontiers in Cellular and Infection Microbiology, 2020)
Responses to Neoadjuvant chemoradiotherapy (nCRT) and therapy-related toxicities in rectal cancer vary among patients. To provide the individualized therapeutic option for each patient, predictive markers of therapeutic responses and toxicities are in critical need. We aimed to identify the association of gut microbiome with and its potential predictive value for therapeutic responses and toxicities of nCRT in rectal cancer patients. In the present study, we collected fecal microbiome samples from patients with rectal cancer who were treated with nCRT at treatment initiation and just after nCRT. Taxonomic profiling via 16S ribosomal RNA gene sequencing was performed on all samples. Patients were classified as responders (R) versus non-responders (NR). Patients were grouped into no or mild diarrhea (N/MD) and severe diarrhea (SD). STAMP and high dimensional class comparisons via linear discriminant analysis of effect size (LEfSe) were used to compare the compositional differences between groups. Phylogenetic Investigation of Communities by Reconstruction of Unobserved States (PICRUSt) was utilized to predict differences in metabolic function between groups. Ten patients were classified as R and 12 patients were classified as NR. Fourteen patients experienced N/MD and 8 patients experienced SD. Several bacteria taxa with significantly different relative abundances before and after nCRT were identified. Similarly, several baseline bacteria taxa and predicted pathways with significantly different relative abundances between R and NR or between N/MD and SD were identified. Specifically, Shuttleworthia was identified as enriched in R and several bacteria taxa in the Clostridiales order et al were identified as enriched in NR. Pathways including fatty acid metabolism were predicted to be enriched in R. In addition, Bifidobacterium, Clostridia and Bacteroides et al were identified as enriched N/MD. Pathways including primary bile acid biosynthesis were predicted to be enriched in N/MD. Together, the microbiota and pathway markers identified in this study may be utilized to predict the therapeutic responses and therapy-related toxicities of nCRT in patients with rectal cancer. More patient data is needed to verify the current findings and the results of metagenomic, metatranscriptomic and metabolomic analyses will further mine key biomarkers at the compositional and functional level.